The Contribution of the Traditional Game of Gobak Sodor to the Holistic Development of Students at Al-Jihadiah Religious Primary School - Hidayat, Muhammad Ferdiansyah; Putra, Ranu Baskora Aji (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. The application of the traditional game of Gobak Sodor in religious primary schools plays an important role as a holistic educational method, but its effectiveness in student development needs to be empirically proven. Materials and methods. This study used a quantitative descriptive design to analyse the impact of this game on affective, cognitive, and psychomotor development. The research subjects involved 30 third-grade students at a religious primary school in Malaysia, selected using a saturated sampling technique (the entire population was used as the sample). Data were collected through direct observation using assessment instruments that had been tested for validity and reliability to ensure data accuracy. Results. Descriptive analysis results showed that students achieved high scores in social attitude (Mean=3.10) and individual motor skills (Mean=2.70), but scores in thinking strategies and teamwork were still relatively low (Mean=2.20). Conclusion. This study makes an important contribution to future studies by confirming that the development of higher-order thinking skills in traditional games does not occur automatically, but requires active instructional guidance from teachers (instructional scaffolding), rather than passive supervision.